Caffeine and performance - Spriett, L. L. (International Journal of Sport Nutrition and Exercise Metabolism, 1995)
Caffeine ingestion (3-9 mg/kg body weight) prior to exercise increases performance during prolonged endurance exercise and short-term intense exercise lasting approximately 5 min in the laboratory. These results are generally reported in well-trained elite or recreational subjects. However, there is a lack of well-controlled field studies to determine the applicability of laboratory results to the athletic world. Caffeine does not appear to enhance performance during incremental exercise tests lasting 8-20 min and during sprinting lasting less than 90 s, although research examining sprinting is rare. In addition, the mechanisms responsible for any improvement in endurance and short-term exercise have not been clearly established. The ergogenic effects of caffeine are present with urinary caffeine levels that are below the limit of 12 micrograms/ml allowed by the International Olympic Committee, which raises serious ethical issues regarding the use of caffeine to improve athletic performance. One solution would be to add caffeine to the list of banned substances, thereby requiring athletes to abstain from caffeine ingestion 48-72 hr prior to competition.